Effects of reduced rates of phosphorus and sulphur on the growth and yield of BRRI dhan29 - Islam, SM Ashiful; Hashem, Md Abul; Hoque, Tahsina Sharmin; Islam, Md Rafiqul (Asian Journal of Medical and Biological Research, 2021)
Balanced fertilization is a pre-requisite for better rice production and it is necessary to determine optimum combination of nutrient elements for application. An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during Boro season to investigate the effects of reduced rates of phosphorus (P) and sulphur (S) on the growth, yield, nutrient content and uptake by rice. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications and eight treatments viz. T1: Control, T2: Recommended Fertilizer Dose (RFD), T3: RFD -20% P, T4: RFD-40% P, T5: RFD-20% S, T6: RFD-40% S, T7: RFD-20% PS and T8: RFD-40% PS. The recommended fertilizer doses were 125 kg N ha-1, 25 kg P ha-1, 70 kg K ha-1, 15 kg S ha-1 and 3 kg Zn ha-1 supplied from urea, TSP, MoP, gypsum and zinc sulphate, respectively. There was significant effect of reduced rates of P and S fertilizers on rice yield compared to control. The highest grain yield of 5.10 t ha-1 and straw yield of 7.02 t ha-1 were recorded from treatment T2 (RFD) that produced the maximum values of all the yield components and the highest content and uptake of nutrients. The performance of T2 and T3 (RFD - 20% P) was statistically similar in producing yield parameters, yields, nutrient contents and uptake by rice. Again, 20% reduced rate of S (T5) or of P and S (T7) caused significant yield reduction, poor yield parameters and less nutrient uptake compared to T2. Thus, the recommended fertilizer dose and the treatments where 20% P was reduced from the RFD are equally efficient in increasing yield as well as enhancing nutritional quality of rice. This reduction of chemical fertilizer could help lessen the cost of rice production with decreasing environmental risk. Asian J. Med. Biol. Res. March 2021, 7(1): 40-47